2015
DOI: 10.1016/j.jmarsys.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the hydrographic conditions and cyst beds in the San Jorge Gulf, Argentina, that favor dinoflagellate population development including toxigenic species and their toxins

Abstract: The overlay of cooler nutrient enriched Beagle-Magellan water with warmer nutrient depleted shelf water and a strong stratification of the water column in the San Jorge Gulf region, Argentina, coincided with relatively high dinoflagellate abundances in April 2012, up to 34,000 cells L −1 . This dinoflagellate proliferation was dominated by Ceratium spp., but environmental conditions also favored to a lesser amount the occurrence of toxigenic dinoflagellates, such as Alexandrium tamarense and Protoceratium reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
2
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 64 publications
12
51
2
8
Order By: Relevance
“…This distributional pattern coincides with the historical predominance of this species in sub-antarctic waters at temperatures lower than 14 8C (Balech, 1988). The higher cell densities found in the San Jorge Gulf may result from the specific hydrographic conditions present in this area, such as a strongly stratified water column known to favor dinoflagellate cell accumulations (Cloern et al, 2005;Jephson and Carlsson, 2009;Krock et al, 2015). The salinity range (33.2-33.9) in which the highest cell densities were detected corresponds to Argentine shelf waters, which consist mainly of subantarctic waters diluted by continental discharge (Piola and Falabella, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…This distributional pattern coincides with the historical predominance of this species in sub-antarctic waters at temperatures lower than 14 8C (Balech, 1988). The higher cell densities found in the San Jorge Gulf may result from the specific hydrographic conditions present in this area, such as a strongly stratified water column known to favor dinoflagellate cell accumulations (Cloern et al, 2005;Jephson and Carlsson, 2009;Krock et al, 2015). The salinity range (33.2-33.9) in which the highest cell densities were detected corresponds to Argentine shelf waters, which consist mainly of subantarctic waters diluted by continental discharge (Piola and Falabella, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…Phytoplankton abundance showed similar values and trends as previously reported for this region in autumn (Almandoz et al, 2011;Krock et al, 2015). One of the most conspicuous features of the phytoplankton assemblage in PCES was the contrasting change of dominance between diatoms and dinoflagellates during the autumn period.…”
Section: Abundance Of Phytoplankton and Heterotrophic Bacteriasupporting
confidence: 86%
“…Phaeopigment concentrations ranged 0.1-1.2 μg L −1 and were with on average 0.6 ± 0.4 μg L −1 relatively high and similar to those reported for middle and outer shelf waters during early autumn on the Argentine Shelf and waters of Northern Drake Passage (Lara et al, 2010;Krock et al, 2015). Mean DOC and inorganic nutrient concentrations showed statistically significant (p b 0.05) differences among sampled areas (Table 2).…”
Section: Synoptic Trend Of Biogeochemical Bulk Parameterssupporting
confidence: 82%
“…These taxonomic surveys, conducted exclusively by means of light and electron microscopy analyses, have revealed a high species richness at the morphological level (Negri and Inza, 1998;Ferrario et al, 1999Ferrario et al, , 2002Sastre et al, 2001;Almandoz et al, 2007;Sunesen et al, 2009). Similarly, DA has been frequently detected in phytoplankton samples from different zones of the Argentine Sea in the last few years (Negri et al, 2004;Sastre et al, 2007;Cadaillón, 2012;Krock et al, 2015). Indeed, Pseudo-nitzschia blooms have been suggested as potentially responsible for calf mortalities of southern right whales along the Valdés Península Wilson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Pseudo-nitzschia blooms have been suggested as potentially responsible for calf mortalities of southern right whales along the Valdés Península Wilson et al, 2015). During these episodes, DA production was mainly associated with elevated cell densities of P. australis (Negri et al, 2004) or P. fraudulenta (Cleve) Hasle (Sastre et al, 2007), but the co-occurrence of several other Pseudonitzschia species (Cadaillón, 2012;Krock et al, 2015), makes it difficult to unequivocally identify the responsible taxa. Likewise, analyses of DA toxin production of local strains of P. pungens (Grunow ex Cleve) Hasle (Sar et al, 2006) and P. multiseries (Montoya et al, 2008) revealed either negative or positive results, respectively, while DA production for other species found in the Argentic Sea has not been yet evaluated.…”
Section: Introductionmentioning
confidence: 99%